Fibule z cmentarzyska kultury przeworskiej w Wólce Domaniowskiej koło Radomia - Olędzki, Marek (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
The fibulas found at the cemetery in Wólka Domaniowska make a large and highly diversified collection. It consists of 29 specimens (together with the ones preserved in fragments) belonging to 15 different types. The fibulas type M according to J. Kostrzewski are the most numerous and the oldest in the set. 11 specimens of these fibulas were found in 10 graves (Tabl. 1-4, 6-12). As it was revealed during the latest research by T. Dąbrowska, these forms should be dated back from the phase A2/A3 to A3 of the Younger pre-Roman period. The interesting fibula Írom the grave 57 (Tabl. I, 13) dates back to the transitory period from the Early pre-Roman to the Younger Roman period (the phase A3/B1). The fibula can be classified as the type 0 according to Kostrzewski and it probably comes from the Marcomanic Bohemia. The fibula type A.67 (Tabl. I, 14) uncovered in the grave 106 presumably comes from the same territory as the above-mentioned one. This type, numerously appearing in the Roman Danubian provinces, are the basic determinant of the absolute chronology of the beginning of the Roman influences (phase B1a in the territory of the Central Europe Barbaricum. The exemplar unconvered in the grave 12, and known as the type A.68 (Tabl. II, 1) is a form developed from the type A.67. However it should be recognized as a local product (the Przeworsk culture craft). Two similar trumpet fibulas (the type I according to T. Liana) being a typical product of the Przeworsk culture workshops were found in the grave 22 (Tabl. II, 2) and 66 (Tabl. II, 3). They date back to the end of the phase B1. The fragment of the so called eye-shaped fibula (Tabl. II, 8) from the grave 54 is no earlier than from the subphase B1a. A large number of the fibulas (specimens) in the cemetery, such as the type: A.148 (Tabl. II, 9), A.38-39 (Tabl. II, 4-5) and the so called Leonów type (Tabl. II, 6) are representants of the fully-developed phase B2. The fibula deriving from the strongly profiled fibulas (Tabl. II, 4) found in the grave 40 is typologically younger. However its coexistence with the type A.38-39 which is precisely dated make us to accept the fact that it was contemporary with the latter. The interesting bronze fibula, being a Roman provincional import, was found in the cemetery (Tabl. II, 11). It is classified as a plated, enamelled exemplar of the group A according to S. Thomas, which she dates from the end of the 2nd to the beginning of the 3rd century AD. The Polish territory got this type of fibulas from the South, i.e. from the Roman Danubian provinces but they provenance may indicate some further lands situated at the Lower Rhine. Many enamel workshops are proved to have existed there. The exemplar type A.162 found in the rich cinerary grave 101 (Tabl. II, 13) is the youngest among the fibulas uncovered in the cemetery. The specimens of this type, i.e. having a cross-bow construction of their springs are well known from the Wielbark and the Čemjachov cultures territory, as well as, from the Lower Elbe. On the other hand they are scarcely found on the Przeworsk culture terrain, and if so, their chronology is limited to the beginning of the Late Roman period (the phase C1a).